PROCESS CONTROL IN THE EDUCATION OF ORGANIC CHEMICAL TECHNOLOGY - Csontos, lstván; Department of Organic Chemical Technology, Budapest University of Technology and Economics (2013)
Laboratory practices for demonstrating the importance of advanced process control methods in the organic chemical technologies have been elaborated. It required the development of a system tha tintegrates the advantages of a reaction calorimeter and a model system of industrial controlled reactors. The hardware and software configuration support the transfer of elaborated control programs of reactions from laboratory level to the industrial technology. General control algorithms of diazotization and chloromethylation can be successfully applied in laboratory practices for forming benzenediazonium chloride and diethoxybenzyl chloride respectively.